Classroom Activities of Trainee English Teachers in Nepal - Kshetree, Arun Kumar (KMC Journal, 2023)
The classroom activities refer to the techniques and activities used by the teacher in the classroom to teach the topic of the day. This article is based on the observation of the classroom activities of the trainee teachers while teaching English. In this study, I have presented what actually the trainee English teachers of the basic level schools of Butwal Sub-metropolitan City tried to do to make their students feel easy in learning English. Based on the classroom observation, the activities of the teachers have been categorized in three major categories namely starting the lesson, lesson or content delivery and closing the lesson. The activities observed during the class observation of the trainee teachers have been presented with some theoretical bases related to the activities. In fact, the students of the Bachelor’s Level of Education have to teach the students as the trainee teachers for just two weeks in the schools around the campus and their classes are observed by their internal observer as well as by an external examiner. The study is basically a descriptive study based on the observation method. I have observed the classes of many of the trainee teachers of English as an external examiner and as an internal observer and have found that their activities were not as expected by the university curriculum. This suggests that the trainee teachers need to be familiar with different kinds of techniques and activities useful to teach English in the classroom and the courses need to be designed to motivate the student teachers use creative ideas to apply the techniques and activities to help their students learn English easily.